Reorganisation of a mesophilic biogas microbiome as response to a stepwise increase of ammonium nitrogen induced by poultry manure supply. (May 2016) - Alsouleman, Khulud; Linke, Bernd; Klang, Johanna; Klocke, Michael; Krakat, Niclas; Theuerl, Susanne
Highlights: Process-risk feedstocks such as poultry manure have to be used with caution. Low amounts of NH4 + -N and VFA favour a Bacteroidetes – Methanosaetaceae microbiome. The addition of 50% poultry manure led to a reconstruction of the microbiome. The functional redundant microbiome was Clostridiales – Methanobacteriaceae -dominated. A natural-regulated microbial diversity management was recorded. Abstract: An anaerobic digestion experiment was investigated to evaluate the impact of increasing amounts of ammonium nitrogen due to poultry manure addition on the reactor performance, especially on the microbiome response. The microbial community structure was assessed by using a 16S rRNA gene approach, which was further correlated with the prevalent environmental conditions by using statistical analyses. The addition of 50% poultry manure led to a process disturbance indicated by a high VFA content (almost 10 gHAc-Eq  L −1 ) in combination with elevated concentrations of ammonium nitrogen (5.9 g NH4 + -N kgFM −1 ) and free ammonia (0.5 g NH3  kgFM −1 ). Simultaneously the microbiome, changed from a Bacteroidetes -dominated to a Clostridiales -dominated community accompanied by a shift from the acetoclastic to the hydrogenotrophic pathway. The "new" microbial community was functional redundant as the overall process rates were similar to the former one. A further increase of poultry manure resulted in a complete process failure.